The art and technique of digital color correction - Hullfish, Steve (Oxford : Focal, 2012)
Guide to the art and technique of color correction based on the invaluable knowledge of more than a dozen of the top colorists in the world. This book allows you unprecedented access to the way the masters of the craft approach their work. Containing decades of industry experience and professional colorist know-how, this book provides an understanding of what top-tier colorists look for in an image and how they know what to do to make it great. Featuring techniques performed in a variety of color correction software applications (DaVinci Resolve, Apple Color, Synthetic Aperture's Color Finesse, and more), this book turns what has long been a misunderstood "black art" into a set of skills that any colorist, editor, independent filmmaker, or motion graphics artist can begin to master. Packed with explanations, tips, and concepts that build on each other.
Includes index.
Keywords: Color photography -- Digital techniques; Color cinematography; Digital video -- Editing; Color computer graphics